Economic benefits of water resources based on input–output model - Zhonghui Dong; Shanshen Li; Peiyu Zhao (Water Supply, 2023)
To relieve environmental stress on water resources and promote stable socio-economic development, this article combined input–output models to analyze water resource utilization and development and to classify economic benefits. Based on this, an in-depth study was conducted on the economic benefits of water resources. Taking Hubei Province as an example, from the perspective of industrial structure, an empirical analysis was conducted on the water use benefits of various industries through input–output of water resources. The results showed that the mechanical industry and the transportation industry had the highest relative output coefficients, reaching 12.17 and 15.21, respectively. According to the results, the economic benefits of water resources in the secondary and tertiary industries of Hubei Province were relatively ideal. In practical development, industry-leading advantages could be utilized to optimize water resources management, innovate water use models and technologies, promote the improvement of agricultural water utilization rate and thus promote sustainable development of water resources. HIGHLIGHTS Water resources are the fundamental element of the ecological environment and an important support for agricultural development.; To relieve environmental stress on water resources and promote stable socio-economic development, this article combined input–output models to analyze the water resources.;